Onomatopoeias of contemporary Ukrainian poetry in the aspect of artistic synthesis - Naumenko, Nataliia (My University, 2020)
The associative conceits, evoked by a concrete image in an author, a reader, or a speaker of a free-verse lyrical work, often get divergent, bearing a resemblance to the complicated system of concentric circles. However, they would converge on the certain level of perception, owing to the fact that the coincidences of associative fields are able to reveal the archetypal content of initial images. Therefore, the artistic imagery of a poetic work synthesizes the visual and audible component in its intonation dimension. This will significantly enlarge the volume of esthetic information, together with the speaker’s emotional attitude which is able to suggest an image expressed in a poem to a reader. Асоціації, які образ, виражений конкретним поняттям, викликає в автора, реципієнта й ліричних персонажів верлібрової поезії, розходяться в різні боки, являючи собою складну систему концентричних кіл. Але на певному рівні сприйняття вони збігаються. Адже на стику асоціативних полів, творених довкола образу, вельми часто приховується первозданне – архетипне його значення. Отже, художня мова вірша має сприйматися як візуально, так і на слух, в інтонаційному звучанні. Це значно посилює обсяг естетичної інформації, додаючи до неї емоційне ставлення мовця та сугестуючи його читачеві.
Keywords: Ukrainian poetry; lyrics; free verse; onomatopoeia; image; nature; synthesis; українська поезія; лірика; вільний вірш; звуконаслідування; образ; природа; синтез; кафедра іноземних мов професійного спрямування